IMPLEMENTASI METODE BERNYANYI DALAM PEMBELAJARAN KOSAKATA BAHASA ARAB PADA ANAK KELOMPOK B DI RA MIFTAHUL HUDA NOGOSARI: IMPLEMENTATION OF SINGING METHOD IN LEARNING ARABIC VOCABULARY IN GROUP B CHILDREN AT RA MIFTAHUL HUDA NOGOSARI - Nahdiyatul Ummah; Hanifa Ayu Ratnaningsih (Jurnal Intelek Insan Cendikia, 2024)
Abstract Language continues to evolve with the changing times, and as a very important communication tool for humans. It is important to teach the language early so that they can speak fluently and understand the language of others. Language can be conveyed through various forms, such as spoken, written, signs, or special symbols. Arabic is an international language that is closely related to Islam and is used by about 20 countries in the world. This thesis discusses the application of singing methods in teaching Arabic vocabulary to group B children in RA Miftahul Huda Nogosari, and analyzes the advantages and disadvantages of these methods in the process of learning Arabic vocabulary in group B children in RA Miftahul Huda Nogosari. In this study, researchers used a qualitative approach with field research methods at RA Miftahul Huda Nogosari. Data collection techniques include observation, interviews, and documentation, involving the participation of educators, learners, and principals as data sources. The results of this study show that the implementation of the singing method before starting core learning or when learners begin to feel bored or bored with the material (ice breaking) this method has several advantages, create a fun and interactive atmosphere, help students in understanding and remembering vocabulary or material taught, as well as expanding participants' Arabic vocabulary without the need to memorize. However, there are also some disadvantages in the use of singing techniques, such as crowds that can interfere with other classes and less effective for students who tend to be quiet. Keywords : Singing method, Arabic vocabulary